Sustainable blends of LDPE/NR and sugarcane bagasse ashes with PE-g-MA thermomechanical relationships [Misturas sosteniveis de PEBD/BN e cinzas de bagaço da cana de açúcar Com PE-g- AM relações termomecânicas] (2019)
e-12411